Designing Ergonomically Equipped Professionalism Equipment for Artists and Orators - Pandey, Nitesh; Kumar Srivastava, Amit; Gupta, Pankaj (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
The beauty of stage is somewhere depended on a piece of equipment called lectern or a stand. The symbol of professionalism depending on the occasion, make it versatile and having many forms. All orators and musicians use various equipment during their presentation. One of the common equipment that is used is a lectern or a podium. Mostly musicians use an adjustable stand which works as a podium for them. The design of that stand for musicians, book readers, etc., should be adjustable and ergonomically so that they can spend more time without any fatigue and pain. It also boosts the confidence and give the structure to the orator with carrying necessary items like notes, laptop etc. Sometimes there is an unavailability of podium stand due to its structure and weight. To solve this problem a multifunction stand is designed with ergonomic concepts. It is an adjustable, lightweight, highly functional, and easy to carry equipment for orators. The design is made to hanger the notes, laptop or necessary tools. The conversion of stand into a small cylindrical shape makes it easy to carry.